KOMUNIKASI PENYULUHAN DINAS TANAMAN PANGAN, HORTIKULTURA DAN KETAHANAN PANGAN DALAM PEMBERDAYAAN KELOMPOK TANI DI KECAMATAN PANGEAN KABUPATEN KUANTAN SINGINGI - Wahyuna, Fitri; Awza, Rusmadi (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2024)
The Department of Food Crops, Horticulture and Food Security's extension plays an important role in improving agricultural capabilities and skills in increasing agricultural yields. This research aims to (1) Understand the knowledge of Pangean District farmers in disseminating information and innovations disseminated by the Kuantan Singingi Regency Food Crops Service, (2) Assess the persuasion of Kuantan Singingi Regency Food Crops Service instructors towards farmers in Pangean District in whether or not they accept the innovations. disseminated, (3) Analyze the decision of farmers in Pangean District to adopt or reject the innovation that is disseminated, (4) Analyze the implementation carried out by farmers in Pangean District when adopting the innovation, and (5) Analyze how farmers in Pangean District confirm when deciding to continue using the innovation or end it. This research uses Everet M. Rogers' Diffusion of Innovation theory. This type of research uses qualitative methods with a descriptive approach. The informants in this study consisted of 6 informants consisting of three farmers, 3 agricultural instructors. The research results show that extension communication is effective in increasing farmers' knowledge and abilities. Farmers who take part in extension programs become more aware and able to use new technology, which results in increased crop yields and the quality of agricultural products. Keywords: Extension, Agricultural Technology Innovation, Farmer Knowledge